(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2024)
The transition to renewable energies aims to reduce the environmental impact of the traditional energy system or of non-renewable energies such as oil and gas. Renewable energies have become an energy sustainability mechanism to ensure energy security for all countries in the world, in particular Algeria", which has good natural energy resources. The study poses the problem of the ecological nature of the solution offered by renewable energies to adapt to environmental change? To ensure that renewable energies are a mechanism for energy sustainability, two components are needed: energy efficiency and sustainable development based on a precise programme planned by the authorities. Renewable energies can also play an important role in climate adaptation, given the urgent need to increase adaptive capacity. Many parties active in international development are integrating climate adaptation into development activities, with the main focus on clean energy activities. Renewable energies are not the magic solution to all the challenges currently facing the world, particularly in terms of food security and preserving environmental safety. However, it has succeeded in making a difference to the process of climate adaptation, or can be seen as the most applicable solution for reducing the use of fossil fuels. For the study to be practical, it must address renewable energy applications relating to food security, such as agrivoltaism. Farming under solar panels. From an environmental point of view, ecological systems are interconnected. If we manage to maintain the Earth’s current temperature without exceeding an additional 1.5 degrees, this will undoubtedly have an impact on the preservation of existing ecological systems in the seas, forests, biodiversity and elsewhere. In this way, we could be taking a step towards preserving the environment. Here, the study focuses on the types of renewable energy programmes that preserve ecological systems.